MEREDAM KEMELUT KONTROVERSI NIKAH SIRRI (Perspektif Maslahah) - Tahir, Masnun (Islamic University of Indonesia, 2010)
At first Islamic-either the Koran or the as-Sunnah are not set in concrete, about the recording of marriage. This is different from the verse muamalah that in certain situations instructed to record it. This is sometimes the legitimacy of certain circles for a wedding or marriage is not registered under the hand (Sirri). Demands of development, with a variety of benefit consideration, the Islamic law in Indonesia, set it as in the discussion of this article. Therefore, discourse is also important that the recording of marriage is a way to protect the rights of wives and children. Because Indonesias strong evidence that marriage is a marriage deed itself. Even the public also needs to be given the understanding that marriage is not listed on the side is not legal under the state also is not valid according to religion. Furthermore, from the standpoint of the State legislation, should be given criminal punishment for couples who do marry are not listed. Keywords: nikah sirri, maslahah, pembaruan, pluralisme hukum